Edukasi Mengenai Pentingnya ASI Eksklusif melalui Metode Ular Tangga - Resifa Nurlaili; Nurfatimah Nurfatimah; Christina Entoh; Desi R Desi R (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The exclusive breastfeeding coverage in Panca Makmur Village has not met the target. Based on a situation analysis from collected data, it was found that the coverage of exclusive breastfeeding in Panca Makmur Village was only 50.7%, while the coverage of exclusive breastfeeding in Dusun 3 was only 38.9%. The aim of this study was to educate pregnant women on the importance of exclusive breastfeeding. The intervention involved a pre-test followed by a snakes and ladders game and a post-test. The evaluation of the post-test questionnaire revealed an increase in pregnant women's knowledge. After the counseling activities, the proportion of participants with good knowledge of exclusive breastfeeding increased from 20% to 80%. These findings suggest that periodic counseling by the village midwife can improve awareness of exclusive breastfeeding among mothers who may not know its importance and may neglect their child's needs.